Consequentialism in the Ethics of Artificial Intelligence - Bouzina, Hanane (Journal of Social Sciences and Humanities, 2025)
This research attempts to clarify the consequentialist ethical approach underlying AI ethics. This approach has produced two different groups regarding the effectiveness of this ethical approach in managing algorithmic systems and achieving the desired well-being. This has led us to examine the reasons behind each group's reservations. Before all that, we provided a semantic overview of normative ethics, of which consequentialism is a subset, along with deontological ethics and virtue ethics, to facilitate the reader's understanding of the rest of the article. The nature of the topic led us to adopt a descriptive analytical approach and a critical approach for a deep and accessible study of the ethics of artificial intelligence, which has become a contemporary problem following the rise of technology. At the end of the research, we reached a number of conclusions, the most important of which was the inadequacy of the ethical consequentialist approach to managing artificial intelligence systems.